STUDIES ON CU2SNS3 THIN FILMS: REVIEW - Ho, Soon Min (2018)
This review emphasizes the preparation of Cu2SnS3 thin films using pulsed laser deposition, spray pyrolysis and successive ionic layer adsorption and reaction method. The advantages and limitations of these techniques were discussed. Some aspects of the characterization of the obtained films were presented also. X-ray diffraction patterns confirm that the growth of various structures of Cu2SnS3 films under different experimental conditions.